IMPACT OF SOME DEVELOPMENTAL VARIABLES ON GDP FOR SELECTED COUNTRIES: A PANEL DATA METHODOLOGY - Adel Salam Kashcool (Scholar Express Journals, 2024)
The gross domestic product (GDP) variable is considered one of the basic variables that measure the economic growth rates of developing or developed countries. These countries are interested in this variable. The research focused on analyzing the relationship between some development variables, which include the foreign direct investment variable and the foreign trade variable, and their impact on the GDP variable for a number of countries including Iraq, Iran, the United Arab Emirates, Saudi Arabia, Kuwait and Malaysia. The sample consists of six countries for a time series extending from 2003 to 2022. The longitudinal section reached 120 observations for the countries subject of the study for the purpose of merging the cross-sectional data with the time series data
Keywords: GDP; foreign trade variable; panel data